2012
DOI: 10.1016/j.mce.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Sodium caprate augments the hypoglycemic effect of berberine via AMPK in inhibiting hepatic gluconeogenesis

Abstract: Berberine (BER), a natural product and active ingredient of genera Berberis and Coptis, has been demonstrated to possess anti-diabetic activities. However, the poor bioavailability of this agent greatly limits its clinical application. In our previous study, we demonstrated that co-administration of sodium caprate, an absorption enhancer, with BER could significantly increase the bioavailability of BER without any serious mucosal damage. Here, we investigated the effects of BER on AMP-activated protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 23 publications
4
53
0
Order By: Relevance
“…In this context, Chang et al (2013) reported that BBR activates AMPK leading to increased glucose transporter-4 (GLUT4) translocation and improved insulin sensitivity in insulin resistant H9c2 cardiomyocytes. In addition, Zhang et al (2012) demonstrated that BBR improved glucose metabolism in diabetic rats by inhibition of gluconeogenesis. In insulin resistant states, BBR inhibited fork head transcription factor O1 (FOXO-1), hepatic nuclear factor 4, and PPARγ coactivator-1α, resulted in suppressed expression of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase, two rate-limiting enzymes in gluconeogenesis (Kim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Chang et al (2013) reported that BBR activates AMPK leading to increased glucose transporter-4 (GLUT4) translocation and improved insulin sensitivity in insulin resistant H9c2 cardiomyocytes. In addition, Zhang et al (2012) demonstrated that BBR improved glucose metabolism in diabetic rats by inhibition of gluconeogenesis. In insulin resistant states, BBR inhibited fork head transcription factor O1 (FOXO-1), hepatic nuclear factor 4, and PPARγ coactivator-1α, resulted in suppressed expression of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase, two rate-limiting enzymes in gluconeogenesis (Kim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It may differ from the final official version of record. and reduced left ventricular myocardium size in rats subjected to experimentally induced cardiac hypertrophy mediated by suprarenal aortic constriction (Chang et al 2012). Moreover, BBR treatment shortened the prolonged action potential duration and reversed inward rectifying potassium ion channel 2 levels to near normal in T2D diabetic rats (Wang et al 2014) .…”
Section: Page 13 Of 39mentioning
confidence: 93%
“…BBR has been shown to improve glucose metabolism in diabetic rats by inhibition of gluconeogenesis (Zhang et al 2012). In insulin resistant liver and kidney BBR inhibited several transcription factors including fork head transcription factor O1, hepatic nuclear factor 4, and peroxisome proliferator-activated receptor-γ coactivator-1α, which in turn suppressed the expression of phosphoenolpyruvate carboxykinase and glucose-6-phosphatase, two rate-limiting enzymes in gluconeogenesis.…”
Section: Page 5 Of 39mentioning
confidence: 99%
“…Fortunately, the researches focusing on the hypoglycemic mechanism showed that metabolic regulator AMPK played an important role in regulating the blood glucose level of type 2 diabetes, and there were many anti-diabetic drugs educing potency by directing the transcriptional section of the gluconeogenic program, such as berberine and metformin [15,24]. It has been documented that AMPK could control blood glucose levels by inhibiting hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%